To explore the effectiveness of atorvastatin in the postoperative formation of collateral blood vessels after encephaloduroarteriosynangiosis in patients with moyamoya disease: a prospective double-blind randomized controlled study - Gao, Gan; Wang, Qian-Nan; Hao, Fang-Bin; Wang, Xiao-Peng; Liu, Si-Meng; Wang, Min-Jie; Han, Cong; Bao, Xiang-Yang; Duan, Lian (Frontiers in Neurology, 2023)
Introduction: The aim of this large, prospective, double-blind randomized controlled trial is to investigate the effect of atorvastatin on the formation of collateral blood vessels in patients after encephaloduroarteriosynangiosis (EDAS) and to provide a theoretical basis for clinical drug intervention. Specifically, we will determine whether atorvastatin has an effect on the development of collateral vascularization and on cerebral blood perfusion after revasculoplasty in patients with moyamoya disease (MMD). Methods and analysis: Overall, 180 patients with moyamoya disease will be recruited and randomly assigned to the atorvastatin treatment group or the placebo control group in a 1:1 ratio. Before revascularization surgery, magnetic resonance imaging (MRI) scanning and digital subangiography (DSA) examination will be routinely performed on the enrolled patients. All patients will receive intervention via EDAS. According to the randomization results, patients in the experimental group will be treated with atorvastatin (20 mg/d, once a day, for 8 weeks) and patients in the control group will be treated with placebo (20 mg/d, once a day, for 8 weeks). All participants will return to the hospital for MRI scan and DSA examination 6 months after EDAS surgery. The primary outcome of this trial will be the difference in the formation of collateral blood vessels revealed by DSA examination at 6 months after EDAS surgery between the two groups. The secondary outcome will be an improvement in the dynamic susceptibility contrast sequence cerebral perfusion on MRI at 6 months after EDAS, compared to the preoperative baseline. Ethics and dissemination: This study was approved by the Ethics Committee of the First Medical Center of the PLA General Hospital. All participates will voluntary provide written informed consent before participating in the trial. Trial registration number: ClinicalTrials.gov ChiCTR2200064976